Potential Development of Sea Cucumber Farming in Tablolong Beach, Kupang, East Nusa Tenggara - suleman; Djonu, Asriati; Kautsari, Neri (International Journal of Applied Research and Sustainable Sciences, 2023)
Tablolong Beach, Kupang, West Nusa Tenggara, has significant potential for sea cucumber aquaculture development. This study examines the environmental conditions, climatic factors, and local natural resources that support sea cucumber farming in this area. The results showed that Tablolong Beach has very suitable environmental characteristics for sea cucumber growth, including suitable water temperature and sufficient natural food availability. In addition, the local community has strong traditional knowledge on sea cucumber collection and cultivation. the purpose of this study was to determine the potential and types of sea cucumbers found around Tablolong beach. This research method is an experimental method where samples are taken by diving in the waters of Tablolong beach. Sea cucumber species found consisted of H. atra, H. leucospilota, H. fuscocinerea, and S. monoturbeculatus. This research provides an important basis for designing a sustainable sea cucumber aquaculture development plan in Tablolong Beach, integrating ecological, economic, and social aspects. By utilizing the natural potential and local knowledge, the development of sea cucumber aquaculture in this area can become a model for sustainable utilization of marine resources and support the livelihoods of coastal communities